Alkyl thiol grafted silver nanoparticle–decorated cellulose nanocrystals on poly(lactic acid) composites for enhanced antibacterial activity and toughening effects. (December 2022) - Song, Lili; Guo, Yunfeng; Fan, Jing; Fan, Xinyan; Xie, Yanjun; Xiao, Zefang; Wang, Haigang; Liang, Daxin; Wang, Yonggui
Graphical abstract: Highlights: Alkyl thiol-grafted Ag NPs decorated CNCs (ATx -Ag-CNCs) were prepared. ATx -Ag-CNCs were used as nanofillers to improve the toughness of PLA. Both antibacterial and toughening properties of PLA were significantly enhanced. PLA/ATx -Ag-CNC leads to the elongation at break of up to 164%. The antibacterial performance against S. aureus indicates a log reduction of 1.6. Abstract: Poly(lactic acid) (PLA), a well-known environmentally friendly polymer, however, due to its brittleness and poor antibacterial properties, it is restricted in several aspects. In this study, alkyl thiol-grafted Ag nanoparticle (NP)-decorated cellulose nanocrystals (ATx -Ag-CNCs) were obtained by modifying Ag NP-decorated CNCs (Ag-CNCs) with 1-decanethiol, 1-tetradecanethiol and 1-octadecanethiol, and the obtained nanocrystals were annotated as AT10 -Ag-CNC, AT14 -Ag-CNC, and AT18 -Ag-CNC, respectively. The hydrophobic alkane chains effectively improved the interfacial interaction between the nanocrystal and PLA. Furthermore, the addition of ATx -Ag-CNCs to a PLA matrix significantly enhanced antibacterial activity on bacteria. The results show that the PLA/AT10 -Ag-CNC-1% composite film displayed the best elongation at a break of 164.46%, which was 16 times higher than that of pure PLA. Moreover, the PLA/ATx -Ag-CNC-5% composite films all exhibited the highest antibacterial activity with a value of 1.6 log CFU/cm 2 against S. aureus .